Can Sleeping Disorder Continue Despite Hypothyroidism Levothyroxine Therapy Be a Marker for Depression? - Özen, Murat Eren; Örüm, Mehmet Hamdi; Öner, Ramazan İlyas; Kalenderoğlu, Aysun; Atmaca, Murad (Adıyaman Üniversitesi, 2018)
Aim: The aim of this study was to investigate the frequency of depressive symptoms in patients with primary hypothyroidism, to determine the degree of recovery of these symptoms after levothyroxine (LT4) treatment, and to assess the presence of predictive symptoms.Methods: 140 women with primary hypothyroidism were evaluated with the Beck Depression Inventory (BDI). All were treated with LT4 alone. Thyroid stimulating hormone (TSH) value was tested after treatment and patients with previous depressive symptoms were reevaluated with BDI.Results: In our study, it was shown that 72 (51.4%) patients had depressive symptoms and 68 patients (48.6%) did not have depressive symptoms (BDI=22.8±1.1, TSH=19.1±3.7 iU/ml, (BDI=8.7±0.6, TSH=12.0±1.2 iU/ml, age (year)=45.0±2.2). After the treatment of primary hypothyroidism, BDI was reapplied in 72 patients with depressive symptoms (1.54 iU/ml±0.31 after TSH) in the first part of the study and depressive symptoms of 54 patients (75%) were found to be absent (BDI=9.0±1.0, TSH=1.59±0.31 iU/ml, age (years)=45.0±2.0). Depressive symptoms persisted in 18 (25%) of the patients (BDI=23.0±2.0, TSH=1.28±0.31 iU/ml, age (year)=42.0±2.0). Sleep disturbance, item 16, is the only persistent persistence after treatment (p>0.045). Conclusion: 51.4% of hypothyroidism patients showed depressive symptoms. Hypothyroidism therapy was sufficient to bring the levels of TSH to normal levels in all cases and to reverse the depressive symptom in 75% of cases. Continuation of sleep disturbance in the remaining 25% of the group may be considered a predictive, unresponsive symptom, and indicates that reassessment of the diagnosis and consideration of the inclusion of another treatment should be considered.

Amaç: Bu araştırmanın amacı, primer hipotiroidizmi olan hastalarda depresif semptomların sıklığını araştırmak, bu semptomların levotiroksin (LT4) tedavisi sonrası iyileşme düzeyini belirlemek ve öngörücü semptomların varlığını değerlendirmektir. Yöntemler: 140 primer hipotiroidizmi olan kadın hasta Beck Depresyon Envanteri (BDÖ) ile değerlendirildi. Hepsi sadece LT4 ile tedavi edildi. Tiroid stimüle edici hormon (TSH) değeri tedaviden sonra test edildi ve daha önce depresif belirtiler gösteren hastalar BDÖ ile tekrar değerlendirildi. Bulgular: Çalışmamızda 72 (%51.4) hastada (BDÖ=22.8±1.1, TSH=19.1±3.7 iU/ml, yaş (yıl)=44.0±2.0) depresif belirti olduğu ve 68 hastada (%48.6) ise olmadığı gösterildi. (BDÖ=8.7±0.6, TSH=12.0±1.2 iU/ml, yaş (yıl)=45.0± 2.2). Primer hipotiroidizmin tedavisinden sonra, çalışmanın ilk bölümünde depresif belirtiler gösteren 72 hastada (TSH sonrası 1.54 iU/ml ±0.31) BDÖ tekrar uygulandı ve 54 hastanın (%75) depresif belirtilerinin ortadan kalktığı görüldü (BDÖ=9.0±1.0, TSH=1.59±0.31 iU/ml, yaş (yıl)=45.0±2.0). Hastaların 18’inde (%25) depresif semptomların devam ettiği görüldü (BDÖ=23.0±2.0, TSH=1.28±0.31 iU/ml, yaş (yıl)=42.0±2.0). Uyku bozukluğu, madde 16, tedaviden sonra belirgin kalıcılığı olan tek faktördür (p > 0.045). Sonuçlar: Hipotiroidizmli hastaların %51.4'ü depresif belirtiler gösterdi. Hipotiroidizm tedavisi tüm olgularda TSH değerlerini normal seviyesine getirmek ve %75'inde depresif belirtileri tersine çevirmek için yeterliydi. Kalan %25’lik grupta uyku bozukluğunun devam etmesi, öngörücü, yanıtsız bir semptom olarak düşünülebilir ve tanıyı tekrar değerlendirmek ve başka bir tedavinin eklenmesini göz önünde bulundurmak gerektiğine işaret eder.
Hipotiroidizmin Levotiroksin ile Tedavisine Rağmen Devam Eden Uyku Bozukluğu Depresyon için Bir Belirteç Olabilir mi?
Keywords: Health Care Administration; Sağlık Kurumları Yönetimi